The Pulsed Electric Field Assisted-Extraction Enhanced the Yield and the Physicochemical Properties of Soluble Dietary Fiber From Orange Peel - Fan, Rui; Wang, Lei; Fan, Jingfang; Sun, Wanqiu; Dong, Hui (Frontiers in Nutrition, 2022)
The study aimed to investigate the effects of pulsed electric field (PEF)-assisted extraction on the yield, physicochemical properties, and structure of soluble dietary fiber (SDF) from orange peel. The results showed that the optinal parameters of PEF assisted extraction SDF was temperature of 45oC with the electric field intensity of 6.0 kV/cm, pulses number of 30, and time of 20min and SDF treated with PEF showed the higher water solubility, water-holding and oil-holding capacity, swelling capacity, emulsifying activity, emulsion stability, foam stability and higher binding capacity for Pb2+, As3+, Cu2+, and higher which resulted from the higher viscosity due to PEF treatment. Compared with the untreated orange peel, the SDF obtained with PEF exhibited stronger antioxidant activities, which was due to its smaller molecular weight (189 vs. 512 kDa). In addition, scanning electron micrograph images demonstrated that the surface of PEF-SDF was rough and collapsed. Overall, it was suggested that PEF treatment could improve the physicochemical properties of SDF from the orange peel and would be the potential extraction technology with high efficiency.